A fully coupled chemo-mechanical cohesive zone model for oxygen embrittlement of nickel-based superalloys. (July 2022) - Auth, Kim Louisa; Brouzoulis, Jim; Ekh, Magnus
Abstract: For nickel-based superalloys subjected to high temperatures and oxygen-rich environments, mechanical loading in combination with oxygen diffusion along grain boundaries leads to an acceleration of crack propagation. To account for these phenomena, a fully coupled thermodynamically consistent chemo-mechanical modeling framework for stress-assisted oxygen embrittlement of grain boundaries in polycrystals is proposed. We formulate an extended cohesive zone model where the grain boundary strength is reduced by the presence of oxygen and the oxygen diffusion is enhanced by tensile mechanical loading. We show that the model can qualitatively predict experimental results such as: reduction of ultimate tensile strength and accelerated crack growth due to dwell time combined with mechanical loading and saturation of crack growth rates for increasing environmental oxygen pressure levels. In addition, numerical simulation results of intergranular crack growth are shown for a 2D polycrystalline structure. An emphasis is put on the difference in cracking behavior after dwelling with or without mechanical loading.